Removal of oil and grease as emerging pollutants of concern (EPC) in wastewater stream - Alade, Abbas O.; Jameel, Ahmed Tariq; Muyibi, Suleyman A.; Abdul Karim, Mohamed Ismail; Alam, Md. Zahangir (IIUM Press, 2011)
Wastewater characteristics, which depend on wastewater source, are increasingly becoming more toxic in recent times. The concentrations of oil and grease in wastewater streams have been observed to increase in wastewater stream with increasing adverse effects on the ecology. This results from the increasing use of oil and grease in high-demanded oil-processed foods, establishment and expansion of oil mills and refineries worldwide, as well as indiscriminate discharge of oil and grease into the water drains, domestically and industrially. This study reports the applications, efficiencies and challenges of the wastewater treatment techniques currently employed in the removal of oil and grease from the industrial wastewater and municipal water stream. The results shows that the concentrations of oil and grease injected into the ecosystem are of higher environmental impact and this needs to be given the desired attention. The desired development for effective removal of oil and grease as emerging pollutants of concern (EPC) in wastewater stream are thus proposed.